Construction of PHB and PHBV multiple-gene vectors driven by an oil palm leaf-specific promoter - Mat Yunus, Abdul Masani; Ghulam Kadir, Ahmad Parveez; Abang Masli, Dayang Izawati; Chan, Pek Lan; Abdullah, Siti Nor Akmar (2009)
One of the targets in oil palm genetic engineering programme is the production of polyhydroxybutyrate (PHB) and polyhydroxybutyrate-co-valerate (PHBV) in the oil palm leaf tissues. Production of PHB requires the use of phbA (β-ketothiolase type A), phbB (acetoacetyl-CoA reductase) and phbC (PHB synthase) genes of Ralstonia eutropha, whereas bktB (β-ketothiolase type B), phbB, phbC genes of R. eutropha and tdcB (threonine dehydratase) gene of Escherichia coli were used for PHBV production. Each of these genes was fused with a transit peptide (Tp) of oil palm acyl-carrier-protein (ACP) gene, driven by an oil palm leaf-specific promoter (LSP1) to genetically engineer the PHB/PHBV pathway to the plastids of the leaf tissues. In total, four transformation vectors, designated pLSP15 (PHB) and pLSP20 (PHBV), and pLSP13 (PHB) and pLSP23 (PHBV), were constructed for transformation in Arabidopsis thaliana and oil palm, respectively. The phosphinothricin acetyltransferase gene (bar) driven by CaMV35S promoter in pLSP15 and pLSP20, and ubiquitin promoter in pLSP13 and pLSP23 were used as the plant selectable markers. Matrix attachment region of tobacco (RB7MAR) was also included in the vectors to stabilize the transgene expression and to minimize silencing due to positional effect. Restriction digestion, PCR amplification and/or sequencing were carried out to ensure sequence integrity and orientation.